Analysis of the Implementation of the Pancasila Student’s Profile for Strengthening Project in the Merdeka Curriculum in Indonesia’s Elementary Schools - Wilsani Wilsani; Faizal Chan; Muhammad Sholeh; Zelly Putriani (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
This research aims to determine how teachers implement the Pancasila Student Profile Strengthening Project in the Independent Curriculum in class V in elementary schools. This research was conducted at Jambi City State Elementary School (SD) 1/IV in the even semester in the academic year of 2022/2023. This research uses a qualitative research methodology with a phenomenological research type. Research data was obtained directly through data collection techniques: observation, interviews, and documentation with the class V homeroom teachers, namely Mrs. S, Mr. AP, Mrs. NEP, Mr. VK, and Mrs. F. After carrying out a series of data collection techniques, the data was then analyzed using the method of Miles and Huberman: reducing data, presenting data, and verifying data. This research shows that in implementing the project to strengthen the profile of Pancasila students, teachers are guided by the guidebook to develop their ways of teaching them through several stages (2022). In the first stage, teachers understand the project for strengthening the profile of Pancasila students. Next, the teacher designs the project to strengthen the profile of Pancasila students. Then, the teacher manages the project to strengthen the profile of Pancasila students. Lastly, the teacher processes the assessment and reports the project results to strengthen the profile of Pancasila students. This research concludes that the fifth-grade teacher at SDN 1/IV Jambi City has successfully implemented the project to strengthen the profile of Pancasila students. It can be seen in the achievement of learning outcomes. Implementing the project to strengthen the profile of Pancasila students can be used as an example for other teachers to implement similar learning.